The use of human monoclonal antibodies to study the structure and function of the West Nile virus prM protein - Calvert, Amanda Elaine, author; Blair, Carol, advisor; Roehrig, John, advisor; Bowen, Richard, committee member; Chisholm, Stephen, committee member (Colorado State University. Libraries, 2012)
Several medically important flaviviruses cause severe disease in humans including West Nile virus (WNV) and dengue viruses (DENVs). No licensed vaccines exist for these viruses, and live-attenuated vaccines may be unsafe in certain populations such as the elderly and immunocompromised. Alternatives to traditional vaccines such as human monoclonal antibodies (hMAbs) would complement prevention and treatment of these diseases. While hMAbs could be used in the prevention and treatment of flavivirus infections, they are also useful tools in expanding our knowledge of the anti-flavivirus human antibody response and the complex antigenic structures of these viruses. In this dissertation production of hybridomas producing hMAbs were attempted, and hMAbs reactive to WNV were used to determine epitopes on the prM protein important in human infection. These epitopes were also studied for their unique involvement in particle secretion and prM presentation. In order to produce hMAbs to flaviviruses a competent human fusion partner cell line, MFP-2, was fused with several different sources of B cells including peripheral blood lymphocytes (PBLs) from people with previous vaccinations or infections with flaviviruses, and splenocytes from humanized mice vaccinated or infected with DENV. hMAbs secreted from hybridomas were able to secrete IgG and IgM antibodies; however, none was specific for anti-flavivirus antibody. Vaccinated and infected humanized mice produced very low and variable levels of virus specific antibody which did not class switch from IgM to IgG even after repeated booster immunizations or secondary infections, a feature consistent with a T-cell independent response. Hybridoma cell lines (2E8, 8G8 and 5G12) producing fully human monoclonal antibodies (hMAbs) specific for the prM protein of WNV were developed using MFP-2 cells and PBLs from a blood donor diagnosed with WNV fever in 2004. Using site-directed mutagenesis of a WNV-like particle (VLP), 4 amino acid residues in the prM protein unique to WNV were identified as important in the binding of these hMAbs to the VLP. Residues V19 and L33 were important amino acids for the binding of all three hMAbs. Mutations at residues T20 and T24 affected the binding of hMAbs 8G8 and 5G12 only. These hMAbs did not significantly protect AG129 interferon-deficient mice or Swiss Webster outbred mice from WNV infection, which was consistent with their inability to neutralize virus infectivity in vitro. While producing mutant WN VLPs to map epitope specificity of these hMAbs, 4 mutations (T20D, K31A, K31V, or K31T) resulted in undetectable VLP secretion from transformed COS-1 cells. K31 mutants formed intracellular prM-E heterodimers; however, these proteins remained in the endoplasmic reticulum, ER-Golgi intermediary compartments and Golgi of transfected cells. The T20D mutation affected glycosylation, heterodimer formation, and WN VLP secretion. When infectious viruses bearing the same mutations were used to infect COS-1 cells, K31 mutant viruses exhibited delayed growth and reduced infectivity compared to WT virus; however, the effect of these mutations on infectious virus was not as dramatic as what was shown in WN VLP. Epitope maps of WN VLP and WNV prM were also different. These results suggest that while mutations in the prM protein can reduce or eliminate secretion of WN VLPs, they have less effect on virus. This difference may be due to the quantity of prM in WN VLPs compared to WNV or to differences in maturation, structure, and symmetry of these particles.
Keywords: flavivirus; prM protein; human monoclonal antibodies